Comparing in vivo bioluminescence imaging and the Multi-Cruzi immunoassay platform to develop improved Chagas disease diagnostic procedures and biomarkers for monitoring parasitological cure. - Amanda Fortes Francisco; Ursula Saade; Shiromani Jayawardhana; Hans Pottel; Ivan Scandale; Eric Chatelain; Peter Liehl; John M Kelly; Maan Zrein (Public Library of Science (PLoS), 2022)
Background Chagas disease is caused by the protozoan parasite Trypanosoma cruzi and is a serious public health problem throughout Latin America. With 6 million people infected, there is a major international effort to develop new drugs. In the chronic phase of the disease, the parasite burden is extremely low, infections are highly focal at a tissue/organ level, and bloodstream parasites are only intermittently detectable. As a result, clinical trials are constrained by difficulties associated with determining parasitological cure. Even highly sensitive PCR methodologies can be unreliable, with a tendency to produce "false-cure" readouts. Improved diagnostic techniques and biomarkers for cure are therefore an important medical need. Methodology/principal findings Using an experimental mouse model, we have combined a multiplex assay system and highly sensitive bioluminescence imaging to evaluate serological procedures for diagnosis of T. cruzi infections and confirmation of parasitological cure. We identified a set of three antigens that in the context of the multiplex serology system, provide a rapid, reactive and highly accurate read-out of both acute and chronic T. cruzi infection. In addition, we describe specific antibody responses where down-regulation can be correlated with benznidazole-mediated parasite reduction and others where upregulation is associated with persistent infection. One specific antibody (IBAG39) highly correlated with the bioluminescence flux and represents a promising therapy monitoring biomarker in mice. Conclusions/significance Robust, high-throughput methodologies for monitoring the efficacy of anti-T. cruzi drug treatment are urgently required. Using our experimental systems, we have identified markers of infection or parasite reduction that merit assessing in a clinical setting for the longitudinal monitoring of drug-treated patients.